Supply Elasticity of Housing - KIM, Kyunghwan (Institutional Knowledge at Singapore Management University, 2012)
The supply elasticity of housing determines how quickly house prices respond to economic shocks and this has many real economic consequences. Malpezzi and Maclennan (2001) describes its importance in housing market analysis: „most housing models, and most policy analysis hinge on explicit or implicit estimates of the price elasticity of supply of housing: does the market respond to demand side shocks with more supply or higher prices‟. However, as pointed out by Quigley (1979), there exist real analytical difficulties in modeling the supply of housing. Attempting to measure the flow of housing services provided by the stock of housing is conceptually pleasing but hard to attempt. Moreover, there is no standard housing unit and each unit can vary considerably on many quality dimensions.